IMPLEMENTATION OF VISITING SERVICES FOR HIGH-RISK PRISONERS IN NARCOTICS PRISON CLASS IIA GUNUNG SINDUR - Isdearko, Dendy; Indahdewi, Lauditta (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the implementation of visitation services for high-risk inmates at Gunung Sindur Class IIA Narcotics Prison. The research focuses on the importance of balancing the fulfillment of inmates' rights with the need for prison security. The research problem lies in how visitation services are applied and the challenges that arise in their implementation. The objective of the study is to gain a deeper understanding of the visitation process and to identify the obstacles encountered during its execution. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The analysis reveals that, although the visitation services have been implemented according to regulations, there are several challenges hindering their effectiveness, including limited facilities, staff shortages, and technical and administrative issues. The study concludes that improvements in human resource management and administrative efficiency are necessary to enhance the quality of visitation services for high-risk inmates. Keywords: High-Risk Inmates; Visitation Services; Narcotics Prison; Strict Supervision